Biological rhythm of saliva ghrelin in humans - Aydin, Suleyman; Ozercan, H. Ibrahim; Aydin, Suna; Ozkan, Yusuf; Dagli, Ferda; Oguzoncul, Ferdane; Geckil, Hikmet (Taylor & Francis Ltd, 2006)
Background: We previously reported that ghrelin in saliva, orexigenic hormone that induces NPY release, was produced and released by salivary glands in humans. The purpose of this study was to investigate a possible circadian rhythm in saliva ghrelin concentration in human subjects as a function of time and meal. Saliva samples were collected at three-hour intervals throughout a 24-h period in 12 healthy volunteer males and ten healthy volunteer females who were provided with meals on a fixed schedule, and saliva collections were made within 15 minutes after each meal. Saliva ghrelin levels were measured by using a commercial radioimmuno assay (RIA) kit that uses I-125-labeled bioactive ghrelin as a tracer and a rabbit polyclonal antibody raised against full-length octanoylated human ghrelin. Immunohistochemical analysis of salivary glands was also performed. The results of this investigation indicated the following. (1) The saliva ghrelin level was slightly higher in female subjects in comparison with male subjects. (2) Saliva ghrelin levels were elevated before each meal and fell to trough levels after eating. (3) Saliva ghrelin levels showed a circadian rhythm that rose throughout the day to a zenith at 0300, then dropped at 0600-0900. (4) Saliva ghrelin also weakly correlated with BMI. (5) Immunohistochemical analysis showed that ghrelin was localized in the striated and excretory ducts of salivary glands of human. The present work is the first report of the circadian rhythm of saliva ghrelin level in human subjects as a function of time and meal. Meal plays an important role in lowering saliva ghrelin concentration in humans. However, present data did not exclude whether the circadian changes in saliva ghrelin expression were regulated by the biological clock or by food intake.
Keywords: salivary glands; saliva; ghrelin; circadian rhythm